2012
DOI: 10.1002/jbm.a.34255
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization, mechanical properties, and in vitro cytocompatibility evaluation of fibrous polycarbonate urethane membranes for biomedical applications

Abstract: This paper reports the electrospinning of a series of oxidatively stable polycarbonate urethanes (PCU) [carbothane (ECT), bionate (EBN), and chronoflex (ECF)] using N,N-dimethyl formamide and tetrahydrofuran as the mixed solvent. The nonwoven membranes were characterized for their structure, performance, and compatibility with cells. Scanning electron microscope was utilized to study the structural morphology and fiber diameter. Microcomputed tomography (micro-CT) was used to characterize the 3D architecture, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…4749 Thus, these devices are not likely to degrade before excretion from the GI tract, as they are composed of materials that degrade on the order of months or longer. 5053 Furthermore, these devices could be tuned to release the majority of their drug payload within an hour (Supporting Information Figure S6), during which time the majority of devices remain bound to GI tissue in ex vivo studies, indicating that these devices could efficiently release their drug payload before passing through the GI tract. Together, the in vitro and ex vivo adhesion assays demonstrated that the nanostraws enhanced adhesion of the drug-releasing device surface to the intestinal epithelium while exposed to fluid flow, indicating that the nanostraws will facilitate prolonged and unidirectional drug release directly toward GI tissue.…”
Section: Resultsmentioning
confidence: 99%
“…4749 Thus, these devices are not likely to degrade before excretion from the GI tract, as they are composed of materials that degrade on the order of months or longer. 5053 Furthermore, these devices could be tuned to release the majority of their drug payload within an hour (Supporting Information Figure S6), during which time the majority of devices remain bound to GI tissue in ex vivo studies, indicating that these devices could efficiently release their drug payload before passing through the GI tract. Together, the in vitro and ex vivo adhesion assays demonstrated that the nanostraws enhanced adhesion of the drug-releasing device surface to the intestinal epithelium while exposed to fluid flow, indicating that the nanostraws will facilitate prolonged and unidirectional drug release directly toward GI tissue.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we evaluated the potential of filamentous TPU as a novel elastic biomaterial. PUs have been used in medicine in various fields as an implantable material because of its excellent biocompatibility and mechanical characteristics . The positive experiences with various PUs in vascular and orthopedic surgery led to the assumption that filaments of the relatively stable polycarbonate urethane could also prove effective as basis for a suture material with possibly superior mechanical characteristics .…”
Section: Discussionmentioning
confidence: 99%
“…PUs have been used in medicine in various fields as an implantable material because of its excellent biocompatibility and mechanical characteristics. 8,20,21 The positive experiences with various PUs in vascular and orthopedic surgery led to the assumption that filaments of the relatively stable polycarbonate urethane could also prove effective as basis for a suture material with possibly superior mechanical characteristics. 21,22 In a previous study, Lambertz et al 23 already showed that laparotomy closure using elastic sutures is feasible, without increasing the risk of burst abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Polycarbonate (PC) has become the fastest growing general engineering plastic among the five engineering plastics due to its good physical and chemical properties, including excellent transparency, high mechanical strength, good thermal stability, and high heat distortion temperature [1][2][3]. Moreover, PC exhibits more superior flame retardancy than ordinary plastics owing to its relatively high limiting oxygen index (22%-25%) and flame-retardant grade (UL-94 V-2) [4,5].…”
Section: Introductionmentioning
confidence: 99%